Predation efficiency of the green lacewings Chrysoperla agilis and C. mutata against aphids and mealybugs in sweet pepper. Issue 2 (9th April 2023) - Koutsoula, Galini; Stamkopoulou, Athanasia; Pekas, Apostolos; Wäckers, Felix; Broufas, George; Pappas, Maria L.
Abstract: Chrysoperla species include well-known predators of aphids and other soft-bodied arthropods. As such, they are considered important biological control agents of herbivorous pests in agroecosystems where many of green lacewings species occur. Despite the high number of species of the genus Chrysoperla, only a few have been assessed for the predation efficiency of their larvae against pests infesting plants, and even fewer are currently marketed for use in biocontrol practice. Difficulties in species identification within the Chrysoperla carnea complex species in particular has been related to varying success of commercial C. carnea s.l. releases in the field. In this study, we assessed the ability of two Chrysoperla species, Chrysoperla agilis a member of the carnea cryptic species group, and Chrysoperla mutata of the pudica group to consume aphid and mealybug individuals and suppress their populations in sweet pepper plants. We found that third-instar larvae of both species were able to consume a high number of aphids (approximately 120 nymphs per larva) and mealybugs (approximately 105 nymphs per larva) within 24 h. Furthermore, the release of second-instar larvae of both C. agilis and C. mutata was shown to be remarkably efficient in suppressing the pest populations in long-term greenhouse experiments. Aphid populations were suppressed by approximately 98% and mealybugs by 78% as compared to control plants. Our results highlight the predation efficiency and the biocontrol potential of two widespread Chrysoperla species for their use in pest control.